Extractable soil nutrient effects on feed quality traits of crop residues in the semiarid rainfed mixed crop-livestock farming systems of Southern India - Haileslassie, Amare; Blümmel, Michael; Wani, S.P.; Sahrawat, Kanwar Lal; Pardhasaradhi, G.; Samireddypalle, A. (Springer, 2013)
In the mixed crop–livestock systems, while general relation among feed quality, productivity and soil nutrient management have been reported, information on the effects of extractable soil nutrients on crop residue (CR) feed quality traits is scarce (e.g. in semiarid regions of Karnataka, India). In view of the increasingly important role of CR as feed components, in these farming systems, generating such information is a relevant research issue for sustainable development. Here, we report the occurrence and strength of relationships among extractable nutrients in soils and CR feed quality traits, and the effects of improved nutrients input on feed availability and feed quality of CR. Soil samples were collected from farmers’ fields in the semiarid zone of Karnataka and analyzed for available phosphorus (P), potassium (K), sulphur (S), zinc (Zn) and boron (B) using standard laboratory methods. Soil test results were clustered as low, medium or high based on the level of nutrient concentration. Four major farming systems involving nine crops and 419 farms were selected for on-farm trials. Under every sample farm, a plot with farmer’s practice (control) and improved fertilizer inputs (combined application of nutrients found deficient by soil testing) were laid. Performance of crops was recorded. Samples were collected for CR feed quality trait analysis using Near Infrared Reflectance Spectroscopy. The result showed that for cereal and oil crops, extractable soil S was significantly negatively associated with anti-feed quality traits such as neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL) (P < 0.01), but significantly positively related to metabolizable energy (ME) and in vitro digestibility (P < 0.01). Extractable B and K levels were associated positively and significantly with NDF, ADF and ADL for oil crops and cereals. Crop level associations, for most crops, showed similar trend. Improved fertilizer inputs affected CR yield much more than it did the quality. It increased ME productivity (ME ha−1) and thereof the potential milk yield ha−1 by as high as 40 % over the control. Therefore, balanced nutrient inputs on crop land positively impact productivity of the livestock compartment of mixed crop–livestock farming system, and this knowledge can build on the currently perceived need and benefits of balanced nutrient replenishment in crop–livestock system.